Pengaruh Pembelajaran Daring Terhadap Kesehatan Mata Di Masa Pandemi - Syifa Aulia Reynanda (Jurnal Komunitas Kesehatan Masyarakat, 2021)
Eyes are sensory organs in humans that have an important role to see and send visual information to the brain. Eyes can work well if they are taken care of properly too, maintain eye health not only by eating nutritious food and vegetables but also doing activities that are healthy. make the eyes feel calm like limiting the use of laptops / devices, too long to expose the screen can cause eye disease due to fatigue. The purpose of this study was to determine the relationship associated with learning subjects. The population and sample in this study were students from various universities in Indonesia, which had 137 people, of which they were students who experienced complaints during daring learning. The type of research used is by using a quantitative survey method which in this method uses a questionnaire to collect samples from a certain population as a tool to collect reference data through questionnaires. In this study, the data used are primary data. From the results of the study, it is stated that during a pandemic, learning greatly affects eye health. It is recommended to rest your eyes by looking at objects around you at a distance of 20 feet or 6 meters for 20 seconds.